The Job Analysis of Civil Servants - V. I. Buyanov (Управление)
This paper has been devoted to the job analysis as the first stage of civil servants’ competencies modeling; the jobs have been correlated with solution of managerial, organizational and economic, organizational and administrative, organizational and methodical, organizational and technical goals and tasks.